2023
DOI: 10.1039/d3fo00882g
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between major foods with added fructose and non-alcoholic fatty liver disease

Abstract: Objectives: The relationship between the consumption of foods with added fructose and non-alcoholic fatty liver disease (NAFLD) was inconsistent in previous epidemiological studies, and no meta-analysis has been performed on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…In our study, the NAFL group exhibited a higher frequency of consumption of products rich in monosaccharides, which is consistent with the findings of Tseng et al, who reported a positive correlation between the consumption of monosaccharides in the form of sweetened beverages and NAFLD occurrence [48]. Based on a meta-analysis of 15 articles encompassing 15,149 individuals, Liu specified that fructose primarily caused liver fat accumulation [49].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the NAFL group exhibited a higher frequency of consumption of products rich in monosaccharides, which is consistent with the findings of Tseng et al, who reported a positive correlation between the consumption of monosaccharides in the form of sweetened beverages and NAFLD occurrence [48]. Based on a meta-analysis of 15 articles encompassing 15,149 individuals, Liu specified that fructose primarily caused liver fat accumulation [49].…”
Section: Discussionsupporting
confidence: 91%